A systematic-ecological approach to Baltic Sea ice studies of algae and protists - Rintala, Janne-Markus (Helsingin yliopisto, 2010)
The seasonal occurrence of sea ice that annually covers almost half the Baltic Sea area provides a unique habitat for halo- and cold temperature-tolerant extremophiles. Baltic Sea ice biology has more than 100 years of tradition that began with the floristic observation of species by the early pioneers using light microscopic techniques that were the only thing available at the time. Since the discovery of life within sea ice, more technologies have become available for taxonomy. Electron microscopy and genetic evidence have been used to identify sea ice biota revealing increased numbers of taxa. Meanwhile ecologists have used light microscopic cell enumeration in addition to the chemical and physical properties of sea ice in attempts to explain the food web structure of sea ice and its functions. Thus, during the Baltic winter, the sea ice hosts more abundant and diverse microbial communities than the water column beneath it. These communities are typically dominated by autotrophic diatoms together with a diverse assortment of dinoflagellates, auto- and heterotrophic flagellates, ciliates, metazoan rotifers and bacteria, which are mostly responsible for the recycling of nutrients. This thesis comprises ecological and systematic studies. In addition to the results of the previous studies carried out on landfast ice, the data presented here provide new insight into the spatial distribution of pelagial sea ice, which has remained largely unexplored. The studies reveal spatial heterogeneity in the pelagial sea ice of the Gulf of Bothnia. There were mismatches in chlorophyll-a concentrations and in photosynthetic efficiencies of the communities studied. The temporal succession was followed and experimental studies performed investigating the community responses towards increased or decreased light in landfast ice in the Gulf of Finland. The systematic studies carried out with established dinoflagellate cultures revealed a new resting cyst belonging to common sea ice dinoflagellate, Scrippsiella hangoei (Schiller) ...